Innovation of Teacher Assessment Standards and Its Impact on Teacher Welfare in the Context of Educational Modernization - Cui, Ying; Wei, Ping (Journal of Research in Vocational Education, 2024)
Teachers play a core role in the process of educational modernization. This paper explores how to improve the sense of belonging, participation and happiness of teachers of different ages, academic qualifications, disciplines and positions by setting diversified teacher assessment standards, so as to give full play to the spirit of educators. The article proposes a series of specific strategies and methods through which private universities can motivate teachers to better develop and contribute and achieve the goal of educational modernization.